2020
DOI: 10.1186/s12931-020-01390-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic fingerprinting and systemic inflammatory profiling of asthma COPD overlap (ACO)

Abstract: Background: Asthma-COPD overlap (ACO) refers to a group of poorly studied and characterised patients reporting with disease presentations of both asthma and COPD, thereby making both diagnosis and treatment challenging for the clinicians. They exhibit a higher burden in terms of both mortality and morbidity in comparison to patients with only asthma or COPD. The pathophysiology of the disease and its existence as a unique disease entity remains unclear. The present study aims to determine whether ACO has a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 77 publications
3
26
1
6
Order By: Relevance
“…A similar discriminatory capacity between asthma and COPD was also observed in other metabolomics studies, using an electronic nose [ 126 ] and peripheral blood [ 127 , 128 ]. In this context, a study involving metabolomic analysis of exhaled air using an eNose in 60 asthma patients (21 with fixed airway obstruction, 39 with “classical”, reversible airway obstruction) and 40 COPD (GOLD stages II–III) showed that external validation of global breath-prints had high accuracy (88% between fixed asthma and COPD; 83% between classical asthma and COPD) for discriminating between the two diseases [ 126 ].…”
Section: Revisiting the “Dutch Hypothesis”: Discriminating Between The “Phenotypes” Of Asthma And Other Chronic Obstructive Airways Diseasupporting
confidence: 82%
See 2 more Smart Citations
“…A similar discriminatory capacity between asthma and COPD was also observed in other metabolomics studies, using an electronic nose [ 126 ] and peripheral blood [ 127 , 128 ]. In this context, a study involving metabolomic analysis of exhaled air using an eNose in 60 asthma patients (21 with fixed airway obstruction, 39 with “classical”, reversible airway obstruction) and 40 COPD (GOLD stages II–III) showed that external validation of global breath-prints had high accuracy (88% between fixed asthma and COPD; 83% between classical asthma and COPD) for discriminating between the two diseases [ 126 ].…”
Section: Revisiting the “Dutch Hypothesis”: Discriminating Between The “Phenotypes” Of Asthma And Other Chronic Obstructive Airways Diseasupporting
confidence: 82%
“…In another study, Ghosh et al [ 128 ] studied metabolic and immunological profiles in ACO, asthma and COPD. As previously mentioned, identification of metabolites was performed using non-targeted metabolomics with the GC–MS technique.…”
Section: Revisiting the “Dutch Hypothesis”: Discriminating Between The “Phenotypes” Of Asthma And Other Chronic Obstructive Airways Diseamentioning
confidence: 99%
See 1 more Smart Citation
“…63 Recently, it was reported that 11 metabolites: serine, threonine, ethanolamine, glucose, cholesterol, 2-palmitoylglycerol, stearic acid, lactic acid, linoleic acid, D-mannose, and succinic acid, were found to be significantly altered in ACO as compared with asthma or COPD. 64 This provides novel insights into metabolic pathways and inflammatory mediators involved in the mechanisms underlying ACO and how these processes may be linked to each other and also with the pulmonary function impairment. Lastly, there are epigenetic changes showing a characteristic expression profile of miRNAs in ACO, distinctive from asthma and COPD.…”
Section: Biomarkers Of Acomentioning
confidence: 99%
“…These consensus definitions included all patients with ACO irrespective of their specific phenotype [11,17,18]. This is particularly relevant because, irrespective of the phenotype, the concept of ACO identifies a group of patients that have some specific genetic [13,19] and epigenetic background [20], differential sputum, serum and exhaled biomarkers [21][22][23] and metabolomics [24]. They also present specific symptoms, different outcomes compared to asthma and COPD and specific response to treatment; basically, they should receive long-acting bronchodilators and ICS [14,19,25].…”
mentioning
confidence: 99%